Entre memórias, resistência e utopia: a Curitiba de Dalton Trevisan - Prates, Jailton Gonçalves (2013)
Cities are built of dreams, bastions, streets, parks, pictures and speeches, carrying with it the desire, the passion and the immediacy of modernity. The urban space, in this sense, is loaded with images, speeches and power, which are encrypted and decrypted constantly. Thus, the urban space is multiple and dissonant, allowing the subject to navigate in paradoxes, which are on the threshold of truth and pretense. The present dissertation discusses issues relevant to urban space, specifically the city of Curitiba, its disposal (urban mapping), its symbols and images that emerge from the official discourse to ratify the popular ideal concepts like "model city", " capital of development "," rare jewelry "," capital of sustainability. " These concepts will be challenged through the narratives of Dalton Trevisan, which feature a Curitiba with no pine, no flowers and no monuments, thus it is not his intention to present this beautiful and wonderful city to "to English people to see"2, but a marginal Curitiba and dystopian populated by poor, vagrants, prostitutes, lunatics, finally, for real men, marked by inequalities, by hunger, pain and anguish. Dalton Trevisan includes the suburbs and misery of man, presenting him as fragmented, hopelessly marginal and exploited. These ideas are arranged in the work-synthesis of Dalton Trevisan, "Em busca de Curitiba perdida" (1992), published on the occasion of the commemoration of the 300th anniversary of the founding of Curitiba, in a form of protest and to show that the city has two sides: the center and margin and this margin echoes the song of lamentation of their Curitiba of yore. In order to give fluency and didactic to the work it were chosen five stories to be analyzed from the theory presented. They are: "Em busca de Curitiba perdida", "Cemitério de elefantes", "Uma negrinha acenando", "Canção do Exílio" e "Curitiba revisitada" .The narratives chosen allow viewing a marginal city, far from Curitiba epic and poetic images and official speeches. What we have is a shameless urban space, in ruins and in constant transformation. Reading the work of Dalton Trevisan enables the vision of a city that resembles a comic opera, in which people struggle to survive. The tone of his work is the complaint, from the negativity of life, as opposed to the beauty of life in the city of Curitiba.